Paper guide tube for cotton slivers and preparation method of paper guide tube
Through the mixed pulp of coniferous wood pulp and broad -leaf wood pulp, combined with the use of modified TIO2 and lubricating rubber fluids, the problem of environmental pollution and discomfort of traditional cotton duct ducts, and realized high -intensity and high -comfortable cotton strips Use a paper catheter.
Patent Information
- Application Number
- CN202411502160.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
The plastic shell of traditional tampon conduits is not easy to degrade, causing environmental pollution, and the hard shell may cause discomfort to the user's physiological structure. At the same time, the strength of the paper material is not high and the surface is rough, resulting in friction and discomfort during use.
Mixing the mixture of coniferous wood pulp and broad -leaved wood pulp, and after the pulp and vacuum dehydration, add the modified TIO2 and lubricating glue to form a tube of cotton strips with high mechanical strength and lubricating surface lubricating.
The environmental protection, safety, and comfort of the cotton ducts is achieved, which is safer and more environmentally friendly than the traditional plastic cotton strip catheter, and improves the mechanical strength and antibacterial properties of the catheter.
Smart Images

Figure BDA0005102891270000111 
Figure BDA0005102891270000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sanitary products, and in particular to a paper conduit for a tampon and a preparation method thereof. Background Art
[0002] In the field of modern sanitary products, tampons are one of the main products used during menstruation and are widely used in women's menstrual care. Traditional tampons are usually made of cotton, synthetic fibers or a mixture of these two materials, and are wrapped in a shell made of plastic or other hard materials. This tampon structure has the following problems: first, the plastic shell is not easy to degrade, causing certain pollution to the environment; second, its hard shell design may cause discomfort to the user's physiological structure.
[0003] Chinese patent document CN117297880A discloses a paper tampon catheter, comprising an inner tube and an outer tube, wherein the outer tube is a hollow structure, a tampon is placed in the outer tube, a hand-held portion is provided at the connecting end of the outer tube and the inner tube, and an insertion end is provided at the other end of the outer tube, and the insertion end is in the shape of a bullet head or a semicircle as a whole; the insertion end comprises a plurality of petal units, each of which is smoothly bent toward the inner side of the outer tube, a splicing seam is left between two adjacent petal units, a molded crack-stop groove is provided at the bottom of the splicing seam, and a petal leaf molded groove is provided below the crack-stop groove, an outer tube stop groove is provided on the hand-held portion of the outer tube, and an inner tube stop groove is provided on the inner tube, and the inner tube is stuck to each other through the inner tube stop groove and the outer tube stop groove and slides in the outer tube. This patent only improves the paper tampon catheter in terms of structure. Since ordinary paper materials generally have low strength and rough surfaces, friction and discomfort will occur during use when used as a tampon catheter, resulting in low user comfort. Summary of the invention
[0004] The main purpose of the present invention is to provide a paper tube for tampons with good mechanical strength and high surface lubricity.
[0005] To achieve the above object, the present invention provides a method for preparing a paper conduit for a tampon, comprising the following steps:
[0006] S1: placing coniferous wood pulp and broadleaf wood pulp in a hydraulic pulper, adding water to adjust the concentration of the pulp, and stirring and mixing to obtain a mixed pulp;
[0007] S2 beats the mixed slurry, then adds additives and modified TiO2, beats, flows onto a screen, then adds it into a mold, vacuum dehydrates, shapes, and dries it to obtain a base paper tube;
[0008] S3: evenly coating the lubricating glue on the inner and outer surfaces of the base paper tube, and drying to obtain the paper tube for the sliver.
[0009] Preferably, in step S1, the mass ratio of coniferous wood pulp to hardwood wood pulp is 2-3:1; and the concentration of the mixed pulp is 4-5wt%.
[0010] Preferably, the beating degree in step S2 is controlled at 45-65° SR.
[0011] Preferably, the auxiliary agent in step S2 is a mixture of sodium carboxymethyl cellulose and polyamide polyamine epichlorohydrin resin; the mass ratio of sodium carboxymethyl cellulose to polyamide polyamine epichlorohydrin resin is 1:2-5.
[0012] Preferably, in step S2, the mass ratio of the auxiliary agent to the modified TiO2 is 1-2:1.
[0013] Preferably, the preparation method of the modified TiO2 is as follows:
[0014] Disperse nano-TiO2 powder in water, add γ-aminopropyltriethoxysilane, and stir at 40-60°C for 2-4h; after the reaction is completed, cool, filter, and collect the solid to obtain pretreated titanium dioxide; take crotonyl chloride and mix it with dichloromethane, pass nitrogen, and stir evenly in an ice-water bath, then add the pretreated titanium dioxide, after uniform dispersion, add triethylamine, heat to room temperature, and stir to react for 8-12h. After the reaction is completed, collect the solid by centrifugation, wash it three times with dichloromethane, and dry it to obtain crotonamide titanium dioxide; disperse the crotonamide titanium dioxide in N, N-dimethylformamide, add 4-vinylbenzyltrimethylammonium chloride and ammonium persulfate, heat at 60-100°C for 6-8h, after the reaction is completed, cool and filter, collect the solid, wash the solid with water and dry it to obtain modified TiO2.
[0015] Preferably, the mass ratio of the nano-TiO2, γ-aminopropyltriethoxysilane, crotonyl chloride, and 4-vinylbenzyltrimethylammonium chloride is 20-30:1:25-35:6-10.
[0016] Nano-TiO2 has strong hiding power and reflectivity, and can significantly improve the whiteness and opacity of paper tubes for tampons. Nano-TiO2 is modified so that the nano-TiO2 has a positive charge and can be adsorbed on the fiber surface, thereby improving its retention rate in the paper tubes for tampons. The preparation of the modified nano-TiO2 is first treated with γ-aminopropyltriethoxysilane to introduce active amino groups on the surface of the nano-TiO2, and then crotonyl chloride is reacted with the active amino groups on the surface of the nano-TiO2 to obtain crotonamide titanium dioxide, and finally the crotonamide titanium dioxide is reacted with 4-vinylbenzyltrimethylammonium chloride to obtain the modified nano-TiO2 of the present invention; the modified nano-TiO2 has good compatibility with the fiber, and the short-chain structure of crotonamide is conducive to improving the bonding toughness between the nano-TiO2 and the fiber, and can better fill the gap between the fiber and combine with the fiber, which is conducive to improving the mechanical strength of the paper tubes for tampons and also makes the paper tubes for tampons smoother.
[0017] Preferably, the coating amount of the lubricating glue in step S3 is 10-15 g / m 2 , the drying temperature is 100-120℃.
[0018] Preferably, the preparation method of the lubricating glue in step S3 is as follows: by mass, 25-60 parts of polyvinyl acetate emulsion, 10-20 parts of potato starch, 4-8 parts of polyvinyl alcohol, 0.1-0.5 parts of potassium sorbate, 1-3 parts of composite lubricant, and 20-65 parts of water are mixed, and then heated and stirred at 80-100° C. for 20-40 minutes to obtain the lubricating glue.
[0019] Preferably, the preparation method of the composite lubricant is as follows:
[0020] The talc powder is dispersed in an ethanol aqueous solution, vinyl trimethoxysilane is added, stirred at 40-60°C for 2-5h, cooled, filtered, the solid is collected, washed and dried to obtain vinyl talc powder; the vinyl talc powder is dispersed in N, N-dimethylformamide, 2-tetradecenoic acid and azobisisobutyronitrile are added, heated to 40-60°C, stirred for 3-4h, filtered after the reaction is completed, and the solid is collected; the solid is added to an aqueous solution of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, stirred for activation, and then diamino silicone oil and N-hydroxysuccinimide are added, heated at 80-100°C for reaction for 4-6h, filtered after the reaction is completed, washed, dried and ground to obtain the composite lubricant.
[0021] Preferably, the mass ratio of the talc, vinyltrimethoxysilane, 2-tetradecenoic acid and bisamino silicone oil is 15-20:2-3:10-18:8-12.
[0022] Talc is a lubricant with strong adsorption capacity. It can adsorb bacteria to its surface and pores. Adding it to the lubricating colloid is beneficial to improving the lubricating performance of the lubricating colloid. The modified talc of the present invention first introduces a carbon-carbon double bond on the surface of the talc, which is beneficial to the addition reaction with 2-tetradecenoic acid and can provide an active carboxyl group. Then, the diamino silicone oil is connected to the talc molecules through a chemical bond. The modified talc is evenly dispersed in the lubricating colloid, which further improves the antibacterial property and lubricating performance of the paper catheter.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1) The present invention provides a paper tampon catheter, which is safe, hygienic, easy to carry and easy to operate. Compared with the traditional plastic tampon catheter, the paper tampon catheter is more environmentally friendly;
[0025] 2) The present invention adds modified TiO2 in the process of preparing the paper conduit for tampons. The modified TiO2 can be adsorbed on the fiber surface, thereby improving its retention rate in the paper conduit for tampons. The modified nano-TiO2 has good compatibility with the fiber, can better fill the gaps between the fibers and combine with the fibers, which is beneficial to improving the mechanical strength of the paper conduit for tampons and making the paper conduit for tampons smoother.
[0026] 3) The present invention can form a lubricating layer on the surface of the base paper tube by coating the lubricating glue on the base paper tube, which is beneficial to the antibacterial and lubricating properties of the paper tube. DETAILED DESCRIPTION
[0027] To avoid redundancy, the items used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.
[0028] The sources of some raw materials used in the present invention are as follows:
[0029] Nano-TiO2, with a particle size of 10-30 nm, was purchased from Nangong Jiuxin New Material Technology Co., Ltd.
[0030] Talc, 325 mesh, was purchased from Tianjin Yandong Haotian Mineral Products Co., Ltd.
[0031] Bisamino silicone oil, with a viscosity of 5000-10000 mPa·s, was purchased from Jining Tangyi Chemical Co., Ltd.
[0032] Example 1
[0033] A method for preparing a paper conduit for a tampon comprises the following steps:
[0034] S1: 600 kg of coniferous wood pulp and 200 kg of broadleaf wood pulp are placed in a hydraulic pulper, water is added to adjust the concentration of the pulp, and the pulp is stirred and mixed to obtain a mixed pulp with a concentration of 5 wt%;
[0035] S2 beats the mixed slurry, and the beating degree is controlled at 50°SR, and then 6kg of sodium carboxymethyl cellulose, 12kg of polyamide polyamine epichlorohydrin resin, and 10kg of modified TiO2 are added, and the mixed slurry is beaten, flowed onto the net, and then added to the mold, vacuum dehydrated, formed, and dried to obtain the base paper conduit;
[0036] S3 evenly coats the inner and outer surfaces of the base paper tube with lubricating glue, and the coating amount of lubricating glue is 12g / m 2 , and then drying at 100° C. to obtain the paper tube for the tampon.
[0037] The preparation method of modified TiO2 in step S2 is as follows:
[0038] Disperse 25kg of nano-TiO2 powder in 50kg of water, add 1kg of γ-aminopropyltriethoxysilane, and stir at 50°C for 3h; after the reaction is completed, cool, filter, and collect the solid to obtain pretreated titanium dioxide; take crotonyl chloride and mix it with dichloromethane, pass nitrogen, and stir evenly in an ice-water bath, then add the pretreated titanium dioxide, after uniform dispersion, add triethylamine, warm to room temperature, and stir the reaction for 10h. After the reaction is completed, collect the solid by centrifugation, wash it three times with dichloromethane, and dry it to obtain crotonamide titanium dioxide; disperse the crotonamide titanium dioxide in N,N-dimethylformamide, add 8.8kg of 4-vinylbenzyltrimethylammonium chloride and 0.6kg of ammonium persulfate, heat the reaction at 80°C for 8h, after the reaction is completed, cool and filter, collect the solid, wash the solid with water and dry it to obtain modified TiO2.
[0039] The preparation method of the lubricating glue in step S3 is as follows: 42 kg of polyvinyl acetate emulsion, 16.8 kg of potato starch, 6.4 kg of polyvinyl alcohol, 0.3 kg of potassium sorbate, 2.3 kg of composite lubricant, and 43.6 kg of water are mixed, and then heated and stirred at 80° C. for 30 minutes to obtain the lubricating glue.
[0040] The preparation method of the composite lubricant is as follows:
[0041] 18 kg of talc powder is dispersed in 100 kg of 50 wt% ethanol aqueous solution, 2.3 kg of vinyl trimethoxy silane is added, stirred at 50° C. for 5 h, cooled, filtered, the solid is collected, washed and dried to obtain vinyl talc powder; vinyl talc powder is dispersed in 100 kg of N, N-dimethylformamide, 16.3 kg of 2-tetradecenoic acid and 0.6 kg of azobisisobutyronitrile are added, heated to 50° C., stirred for 4 h, filtered and solids are collected after the reaction is completed; the solids are added to 0.7 kg of 10 wt% 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride aqueous solution, stirred and activated at 40° C. for 1 h, 10 kg of bisamino silicone oil and 0.5 kg of N-hydroxysuccinimide are added, heated at 90° C. for reaction for 5 h, filtered, washed, dried and ground after the reaction is completed to obtain the composite lubricant.
[0042] Example 2
[0043] A method for preparing a paper conduit for a tampon comprises the following steps:
[0044] S1: 600 kg of coniferous wood pulp and 300 kg of broadleaf wood pulp are placed in a hydraulic pulper, water is added to adjust the concentration of the pulp, and the pulp is stirred and mixed to obtain a mixed pulp with a concentration of 4 wt%;
[0045] S2 beats the mixed slurry, and the beating degree is controlled at 45°SR, and then 3kg of sodium carboxymethyl cellulose, 15kg of polyamide polyamine epichlorohydrin resin, and 12kg of modified TiO2 are added, and the mixed slurry is beaten, flowed onto the net, and then added to the mold, vacuum dehydrated, formed, and dried to obtain the base paper conduit;
[0046] S3 evenly coats the inner and outer surfaces of the base paper tube with lubricating glue, and the coating amount of lubricating glue is 15g / m 2 and then drying at 120° C. to obtain the paper tube for the tampon.
[0047] The preparation method of modified nano-TiO2 in step S2 is as follows:
[0048] Disperse 20.2 kg of nano-TiO2 powder in 50 kg of water, add 1 kg of γ-aminopropyltriethoxysilane, and stir at 60°C for 3 hours; after the reaction is completed, cool, filter, and collect the solid to obtain pretreated titanium dioxide; take 20 kg of crotonyl chloride and mix it with 40 kg of dichloromethane, pass nitrogen, and stir evenly in an ice-water bath, then add the pretreated titanium dioxide, after uniform dispersion, add 1 kg of triethylamine, warm to room temperature, and stir the reaction for 10 hours. After the reaction is completed, collect the solid by centrifugation, wash it three times with dichloromethane, and dry it to obtain crotonamide titanium dioxide; disperse the crotonamide titanium dioxide in 50 kg of N, N-dimethylformamide, add 6.5 kg of 4-vinylbenzyltrimethylammonium chloride and 0.5 kg of ammonium persulfate, heat it at 60°C for 8 hours, after the reaction is completed, cool and filter, collect the solid, wash the solid with water and dry it to obtain modified TiO2.
[0049] The preparation method of the lubricating glue in step S3 is as follows: 25.3 kg of polyvinyl acetate emulsion, 10.1 kg of potato starch, 4.2 kg of polyvinyl alcohol, 0.1 kg of potassium sorbate, 1.2 kg of composite lubricant, and 20 kg of water are mixed, and then heated and stirred at 100° C. for 20 minutes to obtain the lubricating glue.
[0050] The preparation method of the composite lubricant is as follows:
[0051] 15 kg of talc powder is dispersed in 100 kg of 50 wt% ethanol aqueous solution, 2 kg of vinyl trimethoxy silane is added, stirred at 60° C. for 4 h, cooled, filtered, the solid is collected, washed and dried to obtain vinyl talc powder; vinyl talc powder is dispersed in 100 kg of N, N-dimethylformamide, 10.5 kg of 2-tetradecenoic acid and 0.4 kg of azobisisobutyronitrile are added, heated to 40° C., stirred for 4 h, filtered after the reaction is completed, and the solid is collected; the solid is added to 0.6 kg of 10 wt% 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride aqueous solution, stirred and activated at 40° C. for 1 h, then 8 kg of diamino silicone oil and 0.3 kg of N-hydroxysuccinimide are added, heated at 100° C. for reaction for 4 h, filtered, washed, dried and ground after the reaction is completed, and the composite lubricant is obtained.
[0052] Example 3
[0053] A method for preparing a paper conduit for a tampon comprises the following steps:
[0054] S1: 600 kg of coniferous wood pulp and 250 kg of broadleaf wood pulp are placed in a hydraulic pulper, water is added to adjust the concentration of the pulp, and the pulp is stirred and mixed to obtain a mixed pulp with a concentration of 5 wt%;
[0055] S2: beating the mixed slurry, controlling the beating degree at 65°SR, then adding 6kg sodium carboxymethyl cellulose, 15kg polyamide polyamine epichlorohydrin resin, and 10kg modified TiO2, beating, streaming on the net, and then adding it to the mold, vacuum dehydrating, forming, and drying to obtain the base paper conduit;
[0056] S3 evenly coats the inner and outer surfaces of the base paper tube with lubricating glue, and the coating amount of lubricating glue is 10g / m 2 , and then drying at 100° C. to obtain the paper tube for the tampon.
[0057] The preparation method of modified nano-TiO2 in step S2 is as follows:
[0058] Disperse 30kg of nano-TiO2 powder in 50kg of water, add 1kg of γ-aminopropyltriethoxysilane, and stir at 40°C for 4h; after the reaction is completed, cool, filter, and collect the solid to obtain pretreated titanium dioxide; take 35kg of crotonyl chloride and mix it with 40kg of dichloromethane, pass nitrogen, and stir evenly in an ice-water bath, then add the pretreated titanium dioxide, after uniform dispersion, add 1.5kg of triethylamine, warm to room temperature, and stir to react for 8h. After the reaction is completed, collect the solid by centrifugation, wash it three times with dichloromethane, and dry it to obtain crotonamide titanium dioxide; disperse the crotonamide titanium dioxide in 50kg of N,N-dimethylformamide, add 10kg of 4-vinylbenzyltrimethylammonium chloride and 0.7kg of ammonium persulfate, heat at 100°C for 6h, after the reaction is completed, cool and filter, collect the solid, wash the solid with water and dry it to obtain modified TiO2.
[0059] The preparation method of the lubricating glue in step S3 is as follows: 60 kg of polyvinyl acetate emulsion, 20 kg of potato starch, 8 kg of polyvinyl alcohol, 0.5 kg of potassium sorbate, 3 kg of composite lubricant, and 65 kg of water are mixed, and then heated and stirred at 100° C. for 40 minutes to obtain the lubricating glue.
[0060] The preparation method of the composite lubricant is as follows:
[0061] 20 kg of talc powder is dispersed in 100 kg of 50 wt% ethanol aqueous solution, 3 kg of vinyl trimethoxy silane is added, stirred at 60° C. for 4 h, cooled, filtered, the solid is collected, washed and dried to obtain vinyl talc powder; vinyl talc powder is dispersed in 100 kg of N, N-dimethylformamide, 18 kg of 2-tetradecenoic acid and 0.6 kg of azobisisobutyronitrile are added, heated to 40° C., stirred for 4 h, filtered after the reaction is completed, and the solid is collected; the solid is added to 0.8 kg of 10 wt% 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride aqueous solution, stirred and activated at 40° C. for 1 h, 12 kg of diamino silicone oil and 0.5 kg of N-hydroxysuccinimide are added, heated at 100° C. for reaction for 4 h, filtered, washed, dried and ground after the reaction is completed, and the composite lubricant is obtained.
[0062] Comparative Example 1
[0063] A method for preparing a paper conduit for a tampon is similar to the embodiment except that modified TiO2 is not added, and specifically comprises the following steps:
[0064] S1: 600 kg of coniferous wood pulp and 200 kg of broadleaf wood pulp are placed in a hydraulic pulper, water is added to adjust the concentration of the pulp, and the pulp is stirred and mixed to obtain a mixed pulp with a concentration of 5 wt%;
[0065] S2: beating the mixed slurry, controlling the beating degree at 50°SR, then adding 6kg sodium carboxymethyl cellulose and 12kg polyamide polyamine epichlorohydrin resin, beating, streaming on the net, then adding to the mold, vacuum dehydrating, forming, and drying to obtain the base paper conduit;
[0066] S3 evenly coats the inner and outer surfaces of the base paper tube with lubricating glue, and the coating amount of lubricating glue is 12g / m 2 , and then drying at 100° C. to obtain the paper tube for the tampon.
[0067] The preparation method of the lubricating glue in step S3 is as follows: 42 kg of polyvinyl acetate emulsion, 16.8 kg of potato starch, 6.4 kg of polyvinyl alcohol, 0.3 kg of potassium sorbate, 2.3 kg of composite lubricant, and 43.6 kg of water are mixed, and then heated and stirred at 80° C. for 30 minutes to obtain the lubricating glue.
[0068] The preparation method of the composite lubricant is as follows:
[0069] 18 kg of talc powder is dispersed in 100 kg of 50 wt% ethanol aqueous solution, 2.3 kg of vinyl trimethoxy silane is added, stirred at 50° C. for 5 h, cooled, filtered, the solid is collected, washed and dried to obtain vinyl talc powder; vinyl talc powder is dispersed in 100 kg of N, N-dimethylformamide, 16.3 kg of 2-tetradecenoic acid and 0.6 kg of azobisisobutyronitrile are added, heated to 50° C., stirred for 4 h, filtered and solids are collected after the reaction is completed; the solids are added to 0.7 kg of 10 wt% 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride aqueous solution, stirred and activated at 40° C. for 1 h, 10 kg of bisamino silicone oil and 0.5 kg of N-hydroxysuccinimide are added, heated at 90° C. for reaction for 5 h, filtered, washed, dried and ground after the reaction is completed to obtain the composite lubricant.
[0070] Comparative Example 2
[0071] A method for preparing a paper conduit for a tampon is similar to the embodiment, except that the nano-TiO2 is not modified, and specifically comprises the following steps:
[0072] S1: 600 kg of coniferous wood pulp and 200 kg of broadleaf wood pulp are placed in a hydraulic pulper, water is added to adjust the concentration of the pulp, and the pulp is stirred and mixed to obtain a mixed pulp with a concentration of 5 wt%;
[0073] S2: beating the mixed slurry, controlling the beating degree at 50°SR, then adding 6kg sodium carboxymethyl cellulose, 12kg polyamide polyamine epichlorohydrin resin, and 10kg nano-TiO2, beating, streaming on the net, and then adding it to the mold, vacuum dehydrating, forming, and drying to obtain the base paper tube;
[0074] S3 evenly coats the inner and outer surfaces of the base paper tube with lubricating glue, and the coating amount of lubricating glue is 12g / m 2 , and then drying at 100° C. to obtain the paper tube for the tampon.
[0075] The preparation method of the lubricating glue in step S3 is as follows: 42 kg of polyvinyl acetate emulsion, 16.8 kg of potato starch, 6.4 kg of polyvinyl alcohol, 0.3 kg of potassium sorbate, 2.3 kg of composite lubricant, and 43.6 kg of water are mixed, and then heated and stirred at 80° C. for 30 minutes to obtain the lubricating glue.
[0076] The preparation method of the composite lubricant is as follows:
[0077] 18 kg of talc powder is dispersed in 100 kg of 50 wt% ethanol aqueous solution, 2.3 kg of vinyl trimethoxy silane is added, stirred at 50° C. for 5 h, cooled, filtered, the solid is collected, washed and dried to obtain vinyl talc powder; vinyl talc powder is dispersed in 100 kg of N, N-dimethylformamide, 16.3 kg of 2-tetradecenoic acid and 0.6 kg of azobisisobutyronitrile are added, heated to 50° C., stirred for 4 h, filtered and solids are collected after the reaction is completed; the solids are added to 0.7 kg of 10 wt% 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride aqueous solution, stirred and activated at 40° C. for 1 h, 10 kg of bisamino silicone oil and 0.5 kg of N-hydroxysuccinimide are added, heated at 90° C. for reaction for 5 h, filtered, washed, dried and ground after the reaction is completed to obtain the composite lubricant.
[0078] Comparative Example 3
[0079] A method for preparing a paper conduit for a tampon is similar to that of Example 1, except that the composite lubricant is a mixture of talcum powder and amino silicone oil, and specifically comprises the following steps:
[0080] S1: 600 kg of coniferous wood pulp and 200 kg of broadleaf wood pulp are placed in a hydraulic pulper, water is added to adjust the concentration of the pulp, and the pulp is stirred and mixed to obtain a mixed pulp with a concentration of 5 wt%;
[0081] S2 beats the mixed slurry, and the beating degree is controlled at 50°SR, and then 6kg of sodium carboxymethyl cellulose, 12kg of polyamide polyamine epichlorohydrin resin, and 10kg of modified TiO2 are added, and the mixed slurry is beaten, flowed onto the net, and then added to the mold, vacuum dehydrated, formed, and dried to obtain the base paper conduit;
[0082] S3 evenly coats the inner and outer surfaces of the base paper tube with lubricating glue, and the coating amount of lubricating glue is 12g / m 2 , and then drying at 100° C. to obtain the paper tube for the tampon.
[0083] The preparation method of modified nano-TiO2 in step S2 is as follows:
[0084] Disperse 25kg of nano-TiO2 powder in 50kg of water, add 1kg of γ-aminopropyltriethoxysilane, and stir at 50°C for 3h; after the reaction is completed, cool, filter, and collect the solid to obtain pretreated titanium dioxide; take crotonyl chloride and mix it with dichloromethane, pass nitrogen, and stir evenly in an ice-water bath, then add the pretreated titanium dioxide, after uniform dispersion, add triethylamine, warm to room temperature, and stir the reaction for 10h. After the reaction is completed, collect the solid by centrifugation, wash it three times with dichloromethane, and dry it to obtain crotonamide titanium dioxide; disperse the crotonamide titanium dioxide in N,N-dimethylformamide, add 8.8kg of 4-vinylbenzyltrimethylammonium chloride and 0.6kg of ammonium persulfate, heat the reaction at 80°C for 8h, after the reaction is completed, cool and filter, collect the solid, wash the solid with water and dry it to obtain modified TiO2.
[0085] The preparation method of the lubricating glue in step S3 is as follows: 42 kg of polyvinyl acetate emulsion, 16.8 kg of potato starch, 6.4 kg of polyvinyl alcohol, 0.3 kg of potassium sorbate, 2.3 kg of composite lubricant (1.5 kg of talc, 0.8 kg of amino silicone oil), and 43.6 kg of water are mixed, and then heated and stirred at 80° C. for 30 minutes to obtain the lubricating glue.
[0086] Test Case
[0087] Tensile strength test: Referring to GB / T12914-2018 "Constant tension method (20 mm / min) for determination of tensile strength of paper and paperboard", the tensile strength of the paper conduits for tampons prepared in Examples 1-3 and Comparative Examples 1-3 was measured. The specific test data are shown in Table 1;
[0088] Table 1 Test results of tensile strength of paper tube for tampons
[0089]
[0090] It can be seen from the experimental results in Table 1 that the paper conduit for tampons prepared in the present invention has excellent mechanical properties.
[0091] Antibacterial property test: The paper conduits for tampons prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests. Referring to Standard YY0325-2016 and Technical Specifications for Disinfection, the antibacterial properties of the above products were tested by the antibacterial ring test method. Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922) were used as test strains. The incubator temperature was 40°C, the humidity was 60%, and the culture cycles were 1d, 3d, and 5d. The test results are shown in Table 2:
[0092] Table 2 Antibacterial performance test results of paper tubes for tampons
[0093]
[0094] It can be seen from the experimental results in Table 2 that, compared with the comparative example, the tampon paper conduit prepared in the embodiment of the present invention has a good antibacterial property.
[0095] Friction coefficient test: The tampons prepared in Example 1 and Comparative Examples 1-3 were immersed in water with a paper guide tube for 30 seconds and then fixed on a groove plate. Water was injected into the water storage tank until the sample was completely immersed therein. A 200 g standard slider was gently placed above the sample. The slider was dragged by the sensor connecting rod to move at a speed of 100 mm / min. The dynamic friction coefficient was measured. The test results are shown in Table 3:
[0096] Table 3 Friction coefficient test of paper tube for sliver
[0097] Friction coefficient Example 1 0.24 Comparative Example 1 0.33 Comparative Example 2 0.30 Comparative Example 3 0.42
[0098] It can be seen from the experimental results in Table 3 that the paper conduit for tampons prepared in the embodiments of the present invention has good friction performance, which can reduce the friction between the tampon and the vaginal wall, thereby facilitating removal.
[0099] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A method for preparing a paper conduit for a tampon, characterized in that: The steps include: S1: placing coniferous wood pulp and broadleaf wood pulp in a hydraulic pulper, adding water to adjust the concentration of the pulp, and stirring and mixing to obtain a mixed pulp; S2 beats the mixed slurry, then adds additives and modified TiO2, beats, flows onto a screen, then adds it into a mold, vacuum dehydrates, shapes, and dries it to obtain a base paper conduit; S3: evenly coating the lubricating glue on the inner and outer surfaces of the base paper tube, and drying to obtain the paper tube for the sliver.
2. The preparation method according to claim 1, characterized in that: In the step S1, the mass ratio of coniferous wood pulp to hardwood wood pulp is 2-3:
1.
3. The preparation method according to claim 1, characterized in that: The auxiliary agent in step S2 is a mixture of sodium carboxymethyl cellulose and polyamide polyamine epichlorohydrin resin.
4. The preparation method according to claim 3, characterized in that: The preparation method of the modified TiO2 is as follows: Disperse nano-TiO2 powder in water, add γ-aminopropyltriethoxysilane, and stir at 40-60°C for 2-4h; after the reaction is completed, cool, filter, and collect the solid to obtain pretreated titanium dioxide; take crotonyl chloride and mix it with dichloromethane, pass nitrogen, and stir evenly in an ice-water bath, then add the pretreated titanium dioxide, after uniform dispersion, add triethylamine, heat to room temperature, and stir to react for 8-12h. After the reaction is completed, collect the solid by centrifugation, wash it three times with dichloromethane, and dry it to obtain crotonamide titanium dioxide; disperse the crotonamide titanium dioxide in N, N-dimethylformamide, add 4-vinylbenzyltrimethylammonium chloride and ammonium persulfate, heat at 60-100°C for 6-8h, after the reaction is completed, cool and filter, collect the solid, wash the solid with water and dry it to obtain modified TiO2.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the nano-TiO2, γ-aminopropyltriethoxysilane, crotonyl chloride and 4-vinylbenzyltrimethylammonium chloride is 20-30:1:25-35:6-10.
6. The preparation method according to claim 1, characterized in that: The coating amount of the lubricating glue in step S3 is 10-15 g / m 2 , the drying temperature is 100-120℃.
7. The preparation method according to claim 6, characterized in that: The preparation method of the lubricating glue is as follows: by weight, 25-60 parts of polyvinyl acetate emulsion, 10-20 parts of potato starch, 4-8 parts of polyvinyl alcohol, 0.1-0.5 parts of potassium sorbate, 1-3 parts of composite lubricant, and 20-65 parts of water are mixed, and then heated and stirred at 80-100° C. for 20-40 minutes to obtain the lubricating glue.
8. The preparation method according to claim 7, characterized in that: The preparation method of the composite lubricant is as follows: The talc powder is dispersed in an ethanol aqueous solution, vinyl trimethoxysilane is added, stirred at 40-60°C for 2-5h, cooled, filtered, the solid is collected, washed and dried to obtain vinyl talc powder; the vinyl talc powder is dispersed in N, N-dimethylformamide, 2-tetradecenoic acid and azobisisobutyronitrile are added, heated to 40-60°C, stirred for 3-4h, filtered after the reaction is completed, and the solid is collected; the solid is added to an aqueous solution of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, stirred for activation, and then diamino silicone oil and N-hydroxysuccinimide are added, heated at 80-100°C for reaction for 4-6h, filtered after the reaction is completed, washed, dried and ground to obtain the composite lubricant.
9. The preparation method according to claim 8, characterized in that: The mass ratio of the talc powder, vinyl trimethoxysilane, 2-tetradecenoic acid and bisamino silicone oil is 15-20:2-3:10-18:8-12.
10. A paper tube for a tampon, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Paper tampon catheter
CN117297880A